Physical layer security in co-operative MIMO networks - key generation and reliability evaluation - Chen, Kan (Kansas State University, 2016)
Widely recognized security vulnerabilities in current wireless radio access technologies undermine the benefits of ubiquitous mobile connectivity. Security strategies typically rely on bit-level cryptographic techniques and associated protocols at various levels of the data processing stack. These solutions have drawbacks that have slowed down the progress of new wireless services. Physical layer security approaches derived from an information theoretic framework have been recently proposed with secret key generation being the primary focus of this dissertation. Previous studies of physical layer secret key generation (PHY-SKG) indicate that a low secret key generation rate (SKGR) is the primary limitation of this approach. To overcome this drawback, we propose novel SKG schemes to increase the SKGR as well as improve the security strength of generated secret keys by exploiting multiple input and multiple output (MIMO), cooperative MIMO (co-op MIMO) networks. Both theoretical and numerical results indicate that relay-based co-op MIMO schemes, traditionally used to enhance LTE-A network throughput and coverage, can also increase SKGR. Based on the proposed SKG schemes, we introduce innovative power allocation strategies to further enhance SKGR. Results indicate that the proposed power allocation scheme can offer 15% to 30% increase in SKGR relative to MIMO/co-op MIMO networks with equal power allocation at low-power region, thereby improving network security. Although co-op MIMO architecture can offer significant improvements in both performance and security, the concept of joint transmission and reception with relay nodes introduce new vulnerabilities. For example, even if the transmitted information is secured, it is difficult but essential to monitor the behavior of relay nodes. Selfish or malicious intentions of relay nodes may manifest as non-cooperation. Therefore, we propose relay node reliability evaluation schemes to measure and monitor the misbehavior of relay nodes. Using a power-sensing based reliability evaluation scheme, we attempt to detect selfish nodes thereby measuring the level of non-cooperation. An overall node reliability evaluation, which can be used as a guide for mobile users interested in collaboration with relay nodes, is performed at the basestation. For malicious behavior, we propose a network tomography technique to arrive at node reliability metrics. We estimate the delay distribution of each internal link within a co-op MIMO framework and use this estimate as an indicator of reliability. The effectiveness of the proposed node reliability evaluations are demonstrated via both theoretical analysis and simulations results. The proposed PHY-SKG strategies used in conjunction with node reliability evaluation schemes represent a novel cross-layer approach to enhance security of cooperative networks.
Keywords: Physical Layer Security; Cooperative MIMO Networks; Secret Key Generation; Reliability Evaluation; Wireless Communication; Network Tomography